An analysis of the effect that integrated reporting has had on the description of the strategy and strategic planning process in the banking sector in South Africa - Musuwo, Getrude Tafadzwa (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
The study was carried out in order to analyse the effect which the requirement for integrated reporting has had on the description of strategy and strategic planning processes of three South African Banks during the three-year period between 2012 and 2014. The study was conducted in three Johannesburg Stock Exchange listed Banks namely Barclays Bank, Capitec Bank and Standard Bank and focused on their integrated reports for 2012 to 2014. The objectives of the study were to analyse the change in the scope of the depth of reporting on strategy, analyse the evolution of the strategic planning process, compare and contrast the banks' nature, scope and depth of reporting and establish how the requirement for integrated reporting has impacted on the strategic planning processes in the banks. The study was carried out as a content analysis of the integrated reports of the three banks. The sample for the study consisted for the 9 integrated reports issued by the three banks in the period from 2012 to 2014. There was an increasing trend in the prominence of reporting on strategy by the C.E.Os and chairmen of the companies in the integrated reports. All the companies exhibited an increase in the depth of their reporting on strategy in their overall integrated reports. There is a general increase in the depth of reporting on value creation in the integrated reports. From discussing their business models to some extent in 2012 and 2013, all integrated reports reported on strategy to a large extent in 2014. The study concluded that the scope and depth of reporting on strategy was growing. The study also concluded that strategic planning processes had been transformed due to the requirement for integrated reporting. It was also concluded that Standard Bank had the greatest focus on strategy. Further studies may focus beyond strategy and explore the extent to which companies are implementing non-financial measures in their integrated reporting.
Keywords: Uncatalogued